2021
DOI: 10.1017/s1062798721000016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the European Education Area in European Union Integration in Times of Crises

Abstract: The European Union has faced many crises, such as populism, xenophobia, economic and political challenges, to name a few. This has resulted in some questioning whether the EU will survive. Herein, the neo-institutionalist perspective on crises in EU integration frames an original and timely inquiry into the role of a new EU initiative – the European Education Area – in supporting EU integration in these challenging times. This inquiry relies on a thematic analysis of relevant key policy materials. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…One example of such integration is the e-learning policy (Salajan, 2013), another adult education (Milana et al, 2020) where Europeanisation can be observed in polices as well as through formal and informal measures and activities. Indeed, the new EEA 2025, for example, is seen as an instrument for deepening integration as it acts as a tool for structuring and strengthening of the relationships amongst member states (Kushnir, 2022). These changes have been made possible through the ‘open method of coordination’ (OMC) process which does not lead to binding EU legislative measures nor does it require member states to change their law, but it uses a number of soft policy instruments such as standards, benchmarking, peer pressure etc.…”
Section: Introductionmentioning
confidence: 99%
“…One example of such integration is the e-learning policy (Salajan, 2013), another adult education (Milana et al, 2020) where Europeanisation can be observed in polices as well as through formal and informal measures and activities. Indeed, the new EEA 2025, for example, is seen as an instrument for deepening integration as it acts as a tool for structuring and strengthening of the relationships amongst member states (Kushnir, 2022). These changes have been made possible through the ‘open method of coordination’ (OMC) process which does not lead to binding EU legislative measures nor does it require member states to change their law, but it uses a number of soft policy instruments such as standards, benchmarking, peer pressure etc.…”
Section: Introductionmentioning
confidence: 99%
“…This created a mentality which sees an everyday low-level corruption as unavoidable, thus people are relatively tolerant to it and sometimes even do not recognise the manifestations of various types of corruption/bribery considering it "business as usual" (Karklins, 2005). The habit of engaging in shadow activities, primarily bribery, was entrenched in post-Soviet societies and it is now one of the focal factors hindering the value congruence between old and new EU member states which, in turn, is acknowledged as one of the factors obstructing a multifaceted convergence within the EU (Kushnir, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…And the acquisition of higher education, the recognition of qualifications obtained in the country of origin of refugees and their overcoming of language barriers increase their potential and contribution to the socio-economic development of the host country. Education stimulates integration (Kushnir, 2022) and is its tool (Martin & Stulgaitis, 2022). Lack of education, or Revista de Investigación Apuntes Universitarios 2023: 13(1), 301 -318 education acquired in the country of origin, but not recognized by the host country, results in the employment of skilled refugee workers in low-paying non-professional jobs (Santini et al, 2022).…”
Section: Introductionmentioning
confidence: 99%